Predição de ganho genético utilizando índices de seleção em linhagens de milho - Santiago, Silviane de [UNESP] (2014)
Corn is a crop of great importance, occupying a preeminent position both in scientific research and in the world economy, with Brazil being one of the largest grain producers. Increased production and productivity are due in part to the plant breeding programs, where the selection of superior genotypes is performed based on selection indexes. This strategy has been effective for obtaining superior genotypes since it allows to obtain simultaneously gains for many traits of agronomic/economic importance. Thus, the objectives of this work consisted in measuring the genetic gain from selection of lines, which is based on selection indexes , and to compare the efficiency of different indexes to check which one (s) is (are) best suited for phenotypic selection of maize lines. For this, 256 lines were evaluated in experiments with repetition in twelve environments. Grain production, prolificacy, lodging and breaking plant, plant height, ear height, relative position of the spike, male and female flowering, and interval between flushes: the characters were considered. Selection intensities of 10 % and 20% for direct selection and for the seven indices under study were applied. The analysis results indicated that direct selection of characters was not effective in selecting superior genotypes. The indices of Smith & Hazel (1943) and Williams (1962) resulted in greater gains for the genotypes evaluated